Table to show different principles of medical services schemes - in contrast - British Medical Association
1937-07-12 1937 1930s 2 pages TABLE TO SHOW DIFFERENT PRINCIPLES OF MEDICAL SERVICES SCHEMES — IN CONTRAST. British Medical Association. 1. That the system of medical service should be directed to the achievement of positive health and the prevention of disease no less than to the relief of sickness. 2. That there should be provided for every individual the services of a general practitioner or a family doctor of his own choice. 3. That consultants and specialists, laboratory services, and all necessary auxiliary services, together with institutional provision when required, should be available for the individual patient, normally through the agency of the family doctor. 4. That the several parts of the complete medical service should be closely co-ordinated and developed by the application of a planned national health policy. Alternative Principles. 1. Availability and Universality. That every facility for Advice on Health, or Disease, whether general or individual, social or personal, whether immediately curative or prophylactic or remotely preventative, should be unreservedly and without charge, available to every citizen, irrespective of age or social status or economic position. 2. Aim Of Highest Skill. That the Medical and ancillary services, necessary in any General Health Scheme, should be the best available in the country, uniformly administered through a Central Government Department or Departments, working in unison with Local Authorities, properly co-ordinated in its different aspects or phases, whether domiciliary or institutional, whether special or specialist, or ordinary or "general medical practitioner of average skill or ability", so that each individual case should have without reserve the appropriate treatment and the highest suitable medical skill, with proper and adequate facilities for any specialist or institutional treatment necessary. 3. Proved Competence of Professional Participants. That from the point of view of the individual patient the competence and skill of the attending practititioner or practitioners, fortified by adequate facilities for the obtaining of proper suitable equipment or higher consultant or specialist opinion, is of more importance than any other principle. 4. Adequate Planning. That the General Health policy of the Nation should be properly and adequately planned, each section linked up to another or others and occupying its appropriate niche, with provision and opportunities for periodic reviewing in all its aspects — from the initial training and post-graduate refreshing of the medical professionals and ancillary vocations to the proper application of the Health Services, properly coordinated and uniformly administered in all regions and districts, rural or urban. 292/847/1/8